From cultural movement to structural equivalence: Modeling graph isomorphism through serampang dua belas dance - Rahmi Ramadhani; Nuraini Sri Bina; Suci Dahlya Narpila; Muhammad Rizky Mazaly; Rusmini Rusmini (Universitas Hamzanwadi, 2026)
This study addresses a limitation in ethnomathematics research, which often does not go beyond identifying visual patterns, by examining how ethnomathematical modeling of traditional dance can illuminate graph isomorphism. Focusing on the Serampang Dua Belas dance of North Sumatra, the study employs a qualitative ethnographic approach, with data collected through performance observations, video documentation, interviews with cultural experts in Serdang Bedagai Regency, and a review of choreographic literature. Movement sequences were analyzed through data reduction, categorization of transition patterns, and reconstruction of spatial–temporal relations, then modeled as directed graphs using GeoGebra. Dancers’ positions were represented as vertices and transitions as directed edges, enabling formal analysis through adjacency matrices and bijective mappings to verify isomorphism. The findings reveal that although the variations differ visually, several segments exhibit structural equivalence across linear, cyclic, and loop-containing graphs. This study advances ethnomathematics toward formal structural verification grounded in graph theory and highlights its potential to support relational understanding in discrete mathematics learning.